The APC I1307K allele conveys a significant increased risk for cancer. Issue 6 (13th October 2015) - Leshno, Ari; Shapira, Shiran; Liberman, Eliezer; Kraus, Sarah; Sror, Miri; Harlap‐Gat, Amira; Avivi, Doran; Galazan, Lior; David, Maayan; Maharshak, Nitsan; Moanis, Serhan; Arber, Nadir; et al.
Abstract : This study is the first attempt to evaluate the association between the APC I1307K variant and overall cancer risk. It is unique in both its large sample size and in the reliability of data in the control group. The findings described in this article have major implications in terms of identifying asymptomatic individuals who are at increased risk to harbor cancer and therefore targeted to be enrolled in specific early detection and prevention programs. The prevalence of the APC I1307K missense mutation among Ashkenazi Jews is ∼6%. Carriers are at an increased risk for colorectal neoplasia. In this study, we examined the association of this variant with non‐colorectal cancers. Consecutive 13, 013 healthy subjects who underwent screening at the Integrated Cancer Prevention Center between 2006 and 2014 were enrolled. This population was supplemented with 1, 611 cancer patients from the same institution. Demographics, medical history, and pathological data were recorded. Mortality data were obtained from the Ministry of Health's registry. The prevalence of APC I1307K in cancer patients and healthy subjects was compared. The APC I1307K variant was detected in 189 (11.8%) cancer patients compared to 614 (4.7%) healthy subjects, reflecting an adjusted age and sex odds ratio (OR) of 2.53 ( p  < 0.0001). History of two or more cancer types was associated with a positive carrier prevalence (OR = 4.38 p  < 0.0001). Males had significantly increased carrier prevalence in lung, urologic, pancreatic, and skin cancers. The carrier prevalence among females was significantly higher only in breast and skin cancers. Female carriers developed cancer at a significantly older age compared to non‐carriers (average 62.7 years vs. 57.8, respectively, p  = 0.027), had better survival rates (HR = 0.58, p  = 0.022) and overall increased longevity (average age of death 78.8 vs. 70.4 years, respectively, p  = 0.003). In conclusion, the APC I1307K variant is a reliable marker for overall cancer risk (OR 2.53). Further studies are needed to evaluate its use for specific cancer types—particularly in males. Female carriers have better prognosis and increased lifespan. Abstract : What's new? While Ashkenazi Jews who carry the APC I1307K variant are at an increased risk for colorectal neoplasia, the potential role of this polymorphism in non‐colorectal carcinomas remains unclear. This study investigates the overall risk for neoplasia among APC I1307K polymorphism carriers in a very large prospective Israeli cohort. The findings suggest that the I1307K variant in the APC gene is a global risk factor for cancer, and mostly in males. Female carriers have a better prognosis, with a relatively increased lifespan. The findings may help identify asymptomatic individuals at increased risk for cancer for enrollment in early detection and prevention programs.